Pengelolaan Objek Wisata Alam Danau Tarusan Kamang Di Kecamatan Kamang Magek, Kabupaten Agam - Silvi Wahyu Ergin Saogo; Alexander Syam; Nisye Frisca Andini; Tiara Suci Ramadhani (Kilau Publishing, 2024)
This study aims to find out how (1) the management of Lake Tarusan and (2) how the management of facilities and infrastructure of natural attractions of Lake Tarusan. This type of research uses qualitative description, while for informants this research uses Purposive Sampling, the informants are Wali Nagari or Wali Nagari Staff, the Community, and also visitors in this Tarusan lake. The explanation for data collection techniques in this study is through (1) observation (2) interviews (3) documentation. As for techniques using (1) data analysis (2) data reduction (3) display data (4) drawing conclusions. The results of the research conducted to find out how the management of Lake Tarusan natural tourism objects can be seen from several aspects, including, (1) the management of Lake Tarusan tourism objects which are the managers, including the people of the area, while for the Regional Government has not fully participated in the management, while for the financial sember obtained for the management of Lake Tarusan objects is obtained from community fees and also donations from prospective Calek in the region (2) the management of facilities and infrastructure in the previous Tarusan Lake natural attractions has not been well organized, it is due to the lack of incoming costs and attention from the Regional Government, the management of Lake Tarusan attractions has not been satisfactory both in terms of facilities such as prayer rooms, toilets and seating for visitors. Meanwhile, in terms of infrastructure that is still lacking, namely road access that needs to be expanded, then transportation to get to Lake Tarusan can be .